Anger Management in Improving Teacher Performance in School - Rozi, Fathor; Baharun, Hasan; Tohet, Moch; Aini, Qurrotul; Imamah, Najmi Nurul (JURNAL AL-TANZIM, 2022)
Anger is often a weapon for all creatures to defend their lives through the most natural way or mechanism, namely attacking other animals who are bullies or threats, not even a teacher, also has an angry agent like other living creatures. This study aims to examine anger management to manage anger for PAUD teachers to conduct the learning process calmly, not depressed, and not stressful for children. This research uses qualitative methods of this type of case study with a purposive sampling approach conducted at the Raudhatul Athfal Nurul Islam Kalibuntu Probolinggo institute. The informants in the study were principals, group A teachers, and group B teachers. Results from anger management research in improving teacher performance in schools show that first, analyze the causes of the problem. Second, personal approach and place oriented. Third, reflection so that every teacher knows the extent of their ability to manage anger. The implication is that teachers should remind each other in controlling emotions, especially when in the school environment.